Prenatal cannabinoid exposure affects central cardiorespiratory control in young male and female rats - Patrone, Luis Gustavo A [UNESP]; Karlen-Amarante, Marlusa; Gargaglioni, Luciane H [UNESP]; Zoccal, Daniel B [UNESP] (American Physiological Society, 2025)
Cannabis use among pregnant women is rising globally, mainly for recreational and medical reasons to relieve symptoms like nausea, vomiting, anxiety, and insomnia. This trend is reinforced by the misconception that its natural origin guarantees safety, along with government policies promoting legalization. However, exposure to cannabinoids in utero can impact normal offspring's neurodevelopment and induce malfunctioning of various physiological systems, including the cardiorespiratory function. The present study investigated whether prenatal cannabinoid exposure disrupts the generation and control of autonomic and respiratory activities in early adulthood. Using in situ preparations of juvenile male and female rats (27-28 days old) exposed to a synthetic cannabinoid (WIN 55,212-2; 0.5 mg/kg/day, n = 4-9) or vehicle (n = 3-10) during gestation, we analyzed the activity of nerves innervating respiratory muscles and blood vessels. We noticed that females receiving WIN prenatally exhibited a reduced excitatory drive (postinspiratory activity, post-I) to laryngeal muscles under resting conditions, suggesting impaired control of upper airway patency. Moreover, males and females exposed to WIN displayed reduced post-I and abdominal expiratory motor activities during stimulation of carotid body chemoreceptors (mimicking low-oxygen situations) or exposure to high carbon dioxide levels, indicating an inability to mount appropriate reflex respiratory motor responses during blood gas disturbances. In addition, WIN-treated males showed attenuated sympathoexcitatory responses to carotid body activation or hypercapnia, evidencing a limited capacity to promote sympathetic-mediated hemodynamic changes. Thus, manipulating the fetal endocannabinoid system impacts the development of networks controlling respiratory and autonomic functions, leading to negative, long-term consequences for ventilation and cardiovascular function.NEW & NOTEWORTHY Cannabis use among pregnant women is rising globally; however, the impact on offspring's homeostatic physiological systems is still uncertain. We found that prenatal cannabinoid exposure impairs respiratory motor control in early adulthood. We also identified that sympathetic control is limited in juvenile males exposed to cannabinoids prenatally. Cannabinoids during pregnancy disrupt offspring's central cardiorespiratory control, highlighting the need for caution regarding cannabis use during pregnancy and its postnatal implications.